PENGARUH PENDEKATAN KETERAMPILAN PROSES DALAM PEMBELAJARAN TEMATIK TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR - Kalista Dela; Kartono Kartono; Siti Halidjah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aims to analyze the effect of the process skills approach in thematic learning on the learning outcomes of fourth grade students at SD Negeri 66 Pontianak Kota. The research method used is the experimental method. Quasi experimental research design with a nonequivalent control group design. The population is all students of class IV 66 Pontianak Elementary School, 41 students. Sampling using simple random sampling technique, the sample obtained is class IV A consisting of 21 students and class IV B consisting of 20 students. In the selection of the experimental and control class is done by lottery that is making two rolls of paper that reads the control class and the experimental class, which is selected as the experimental class is class IV A and as the control class is IV B. The data collection technique is measurement with research instruments in the form of an optional test. double to measure learning outcomes. Based on the calculations obtained, the average post-test learning outcomes of the experimental class 75.45 with the average post-test learning outcomes of the control class of 63.90, then a tcount of 4.284 and ttable (a = 5%) and (dk = 21 + 20 - 2 = 39) equal to 2,023, which means tcount (4,284) ˃ ttable (2,023), then Ha is accepted. Based on the results of the calculation of the effect size obtained by 0.97 which includes high criteria so that the process skills approach gives an effect in thematic learning towards the learning outcomes of fourth grade students at 66 Pontianak Elementary School. Keywords: Influence, Learning Outcomes, Process Skill Approach, Thematic Learning.